2023
DOI: 10.1002/ael2.20100
|View full text |Cite
|
Sign up to set email alerts
|

Cropping systems with perennial vegetation and livestock integration promote soil health

Abstract: Soil health can differ across cropping systems because of variation in edaphic and management factors. We evaluated how biological indicators of soil health (soil organic matter [SOM], permanganate oxidizable carbon [POXC], mineralizable carbon [MinC], autoclaved-citrate-extractable [ACE] protein, and potentially mineralizable nitrogen [PMN]) compared across four common Wisconsin cropping systems: grazed cool-season pastures, forage-based rotations that included perennial legumes or grasses, annual rotations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…While none of our grouping variables explained more than 3% of Cmin variance when considering both agricultural and perennially vegetated sites together (Table 5), we found that considering agricultural soils alone resulted in the grouping variables explaining up to 73% of the observed variance (Table S2). This highlights land use as an important factor driving Cmin in our dataset and is consistent with previous studies that have observed large differences in Cmin when comparing annual agricultural systems with more perennial systems such as pastures (Augarten et al., 2023). In addition, others have found Cmin to be sensitive to soil conditions such as antecedent soil moisture, soil temperature, and vegetation; these are all factors which are expected to differ between agricultural and perennially vegetated sites (Belanger et al., 2021; Das et al., 2019; Martin & Sprunger, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…While none of our grouping variables explained more than 3% of Cmin variance when considering both agricultural and perennially vegetated sites together (Table 5), we found that considering agricultural soils alone resulted in the grouping variables explaining up to 73% of the observed variance (Table S2). This highlights land use as an important factor driving Cmin in our dataset and is consistent with previous studies that have observed large differences in Cmin when comparing annual agricultural systems with more perennial systems such as pastures (Augarten et al., 2023). In addition, others have found Cmin to be sensitive to soil conditions such as antecedent soil moisture, soil temperature, and vegetation; these are all factors which are expected to differ between agricultural and perennially vegetated sites (Belanger et al., 2021; Das et al., 2019; Martin & Sprunger, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, biochar can enhance soil health (Gundale et al, 2016) by improving soil microbiome structure and function (Bahram et al, 2018; Xu et al, 2020), thus resulting in increased underground C cycling and above‐ground productivity. Organic fertilizer amendment (e.g., manure and composts) is one of the most effective measures for sustainable land management, both in agriculture and forestry (Reardon, 2014; Williams, 1942; Yang et al, 2022), and its role in improving soil quality (e.g., physicochemical properties, structure, and microbiome functions), replenishing SOM loss, and minimizing land degradation has been well accepted (Augarten et al, 2023; Jin et al, 2022; Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Permanganate‐oxidizable carbon (POXC) was measured by quantifying absorbance at 550 nm with a spectrophotometer after subjecting duplicate 2.5 g soil to 2 min shaking (120 rpm) in 20 mL of 0.02 M KMnO 4 solution (pH 7.2) followed by a 10 min rest period (Culman et al., 2012; Weil et al., 2003). Here, we consider POXC a chemical SHI, though some have variously classified it as biological given its interpretation as labile C (e.g., Augarten et al., 2023; Martin et al., 2022) despite recent evidence that POXC does not represent labile C (Woodings & Margenot, 2023).…”
Section: Methodsmentioning
confidence: 99%